Motivation and self-concept - Zaichkowsky, Judy (Henry Stewart Talks, 2013)
Motivation, Values, Needs, Wants, Motivational direction, Motivational strength, Maslow’s hierarchy of needs, Consumer involvement, Measuring involvement, Cognitive involvement, Affective involvement, Self-esteem, Real and ideal selves, Consumption and self-conflict, The extended self
Reviewed at 2019/03/28